RISE: A project to provide solar-powered lighting to rural schools in Perak / Dr Nur Azfahani Ahmad - Ahmad, Nur Azfahani (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
A new community-based project, jointly launched by researchers from Universiti Teknologi MARA (UiTM) Perak Branch, assists rural schools in Perak in harvesting energy from the sun for lighting purposes.